Effectiveness of Noninvasive Positive Pressure Ventilation Combined with Enteral Nutrition in the Treatment of Patients with Combined Respiratory Failure after Lung Cancer Surgery and Its Effect on Blood Gas Indexes - Yongjun Zhang; Lanbo Liu; Dawei Li; Dongsheng Zhou (Emergency Medicine International)
Purpose. To investigate the effect of noninvasive positive pressure ventilation (NIPPV) combined with enteral nutrition support in the treatment of patients with combined respiratory failure after lung cancer surgery and its effect on blood gas indexes. Methods. A total of 82 patients with combined respiratory failure after lung cancer surgery who were treated in our hospital from March 2016∼September 2021 were selected as the research subjects, and according to the random number table method, they were equally divided into the parenteral nutrition group (n = 41) with NIPPV + parenteral nutrition support treatment and the enteral nutrition group (n = 41) with NIPPV + enteral nutrition support treatment. The curative effects of two groups after treatment were compared, and the pulmonary function indexes (maximum expiratory pressure (PEmax), maximum midexpiratory flow rate (MMF), and maximum ventilation volume (MVV)), blood gas indexes (blood oxygen partial pressure (PaO2) and partial pressure of carbon dioxide (PaCO2)), oxygen metabolism indicators [mixed venous oxygen tension (PvO2) and central venous oxygen saturation (ScvO2)], nutritional status indicators (hemoglobin (HGB), serum albumin (ALB), and total protein (TP)), and nutritional score before and after treatment in two groups were detected, and the 6-month follow-up of the two groups was recorded. Results. After treatment, the total effective rate of the enteral nutrition group 95.12% (39/41) was higher than that of the parenteral nutrition group 80.49% (33/41) (P<0.05). At 3, 12, 24, and 48 hours after the operation, the levels of PEmax, MMF, and MVV in two groups were higher than those before treatment, and the enteral nutrition group was higher than the parenteral nutrition group at the same time point (P<0.05). At 3, 12, 24, and 48 hours after the operation, the PaO2 levels in two groups were higher than those before treatment, and the PaCO2 levels were lower than those before treatment. The PaO2 levels in the enteral nutrition group were higher than those in the parenteral nutrition group at the same time point, and the PaCO2 levels were lower than those in the parenteral nutrition group at the same time point (P<0.05). At 3, 12, 24, and 48 hours after the operation, the levels of PvO2 and ScvO2 in two groups were higher than those before treatment, and the enteral nutrition group was higher than the parenteral nutrition group at the same time point (P<0.05). After treatment, the levels of HGB, ALB, and TP in two groups were higher than those before treatment, and the enteral nutrition group was higher than the parenteral nutrition group (P<0.05). After treatment, the nutritional scores of the two groups were higher than those before treatment, and the enteral nutrition group was higher than the parenteral nutrition group (P<0.05). At 6-month postoperative follow-up, the incidence of death in the enteral nutrition group 2.44% (1/41) was lower than that of the parenteral nutrition group 17.07% (7/41) (P<0.05). Conclusions. The efficacy of NIPPV combined with enteral nutrition support in treating patients with combined respiratory failure after lung cancer surgery is remarkable. It can improve patients’ pulmonary function and blood gas index, correct patients’ hypoxia status and the patients’ nutritional level was significantly improved, which helped to reduce the mortality rate and improve the prognosis.